MODL-19. Exploiting DNA damage response inhibitors to enhance radiation efficacy in medulloblastoma models. (3rd June 2022) - Dholaria, Hetal; Buck, Jessica; Hii, Hilary; Carline, Brooke; Bryne, Jacob; Kuchibhotla, Mani; Lawler, Jessica; Porter, Gilbert; Whitehouse, Jacqueline; Howlett, Meegan; Gottardo, Nick; Endersby, Raelene
Abstract: Despite treatment intensification, survival for certain high-risk subgroups of medulloblastoma (MB) such as p53 mutant SHH (SHHa) and MYC amplified Group 3 (Gr3) have remained dismal. Recently, the use of Carboplatin as radiosensitiser with craniospinal irradiation (CSI) has shown survival benefit in children with Gr3 MB. However, there is an ongoing need to discover newer, non-chemo radiosensitisers which have minimal toxicity and unequivocal benefit in high-risk MB. Radiation is a potent inducer of DNA damage in cancer cells. CHK1/2, ATR, and WEE1 kinases are critical regulators of the DNA damage response (DDR). We hypothesised that inhibition of these kinases may enhance radiation-induced cytotoxicity in MB. We utilised small-animal radiotherapy platform to deliver CSI to MB-tumour-bearing mice that closely mimic clinical settings. Here we demonstrate systematic preclinical evaluation of DDR inhibitors (DDRi) as radiosensitiser in MB models. In vitro treatment of Gr3 MB cell lines with either CHK1/2 inhibitor (CHKi, Prexasertib, AZD7762), ATR inhibitor (ATRi, AZD6738), or WEE1 inhibitor (WEE1i, AZD1775) along with radiation ceased post-radiation cell cycle arrest, prohibiting DNA repair, and increasing apoptosis. The combination also reduced the colony-forming ability of MB cells post-irradiation. In vivo, CSI and DDRi, each induced modest apoptosis in orthotopically-implanted high-risk MB mice. When these models were treated with CHKi+CSI, ATRi+CSI or WEE1i+CSI, the effect was cumulative. Importantly, addition of DDRi to CSI significantly prolonged the survival of MB-bearing mice compared to CSI alone. Here we also explored strategy of "vertical blockade" by simultaneous use of CHKi and WEE1i which when combined with CSI also prolonged survival in MB-bearing mice. Additionally, we evaluated various regimens to best deliver these novel agents with CSI, maximising effect and minimising toxicity. Our study opens up new realms of radiosensitisation with the use of DDRi in paediatric medulloblastoma and provides robust preclinical evidence for clinical translation.